Cost of hepatocellular carcinoma to the national health service in England: a registry-based analysis. Issue 1 (21st February 2023) - Cullen, Katherine; Jones, Mari; Pockett, Rhys D.; Burton, Anya; Cross, Timothy J.S.; Rowe, Ian A.; Paley, Lizz; Tataru, Daniela; Alexander, Graeme; Marshall, Aileen; Fitzsimmons, Deborah
Abstract : Objective: Hepatocellular carcinoma (HCC) incidence in the UK trebled between 1997 and 2017. With increasing numbers requiring treatment, understanding the likely impact on healthcare budgets can inform service planning and commissioning. The aim of this analysis was to use existing registry data to describe the direct healthcare costs of current treatments for HCC and estimate the impact on National Health Service (NHS) budgets. Design: A retrospective data analysis based on the National Cancer Registration and Analysis Service cancer registry informed a decision-analytic model for England comparing patients by cirrhosis compensation status and those on palliative or curative treatment pathways. Potential cost drivers were investigated by undertaking a series of one-way sensitivity analyses. Results: Between 1 January 2010 and 31 December 2016, 15 684 patients were diagnosed with HCC. The median cost per patient over 2 years was £9065 (IQR: £1965 to £20 491), 66% did not receive active therapy. The cost of HCC treatment for England over 5 years was estimated to be £245 million. Conclusion: The National Cancer Registration Dataset and linked data sets have enabled a comprehensive analysis of the resource use and costs of secondary and tertiary healthcare for HCC, providing an overview of the economic impact to the NHS England of treating HCC.